Diversified Mammalian Visual Adaptations to Bright- or Dim-Light Environments. (17th March 2023) - Gai, Yulin; Tian, Ran; Liu, Fangnan; Mu, Yuan; Shan, Lei; Irwin, David M; Liu, Yang; Xu, Shixia; Yang, Guang
Abstract: Photic niche shifts of mammals are associated with changing visual capabilities, primarily mediated by three visual pigments, two (SWS1 and M/LWS) of them for color vision and rhodopsin (RH1) for dim-light vision. To further elucidate molecular mechanisms of mammalian visual adaptations to different light environments, a systematic study incorporating evolutionary analyses across diverse groups and in vitro assays have been carried out. Here, we collected gene sequences for the three opsins from 220 species covering all major mammalian clades. After screening for cone opsin gene losses, we estimated selective pressures on each of the three genes and compared the levels of selection experienced by species living in bright- and dim-light environments. SWS1 pigment is shown to experience accelerated evolution in species living in bright-light environments as has RH1 in aquatic cetaceans, indicating potential shifts for ecological adaptations. To further elucidate the functional mechanisms for these two pigments, we then carried out site-directed mutagenesis in representative taxa. For SWS1, violet and ultraviolet sensitivities in the pika and mouse are mainly affected by substitutions at the critical sites 86 and 93, which have strong epistatic interaction. For RH1, the phenotypic difference between the sperm whale and bovine sequences is largely contributed by a substitution at site 195, which could be critical for dim-light sensation for deep-diving species. Different evolutionary patterns for the visual pigments have been identified in mammals, which correspond to photic niches, although additional phenotypic assays are still required to fully explain the functional mechanisms.